Evaluation of Serum Ferritin, Procalcitonin, and C-Reactive Protein for the Prediction of Severity and Mortality in Hemorrhagic Fever With Renal Syndrome - Che, Lihe; Wang, Zedong; Du, Na; Li, Liang; Zhao, Yinghua; Zhang, Kaiyu; Liu, Quan (Frontiers in Microbiology, 2022)
This study aimed to analyze the clinical significance of serum ferritin, procalcitonin (PCT) and C-reactive protein (CRP) in hemorrhagic fever with renal syndrome (HFRS) patients. The demographical, clinical and laboratory data in 373 HFRS patients in northeastern China were retrospectively analyzed. The levels of serum ferritin and PCT in severe patients (n=108) were significantly higher than those in mild patients (n=265, p<0.001) and associated with HFRS severity. The area under the receiver operating characteristic curve (AUC) values of serum ferritin and PCT for predicting the severity of HFRS were 0.732 (95% CI 0.678-0.786, p<0.001) and 0.824 (95% CI 0.773-0.875, p<0.001), respectively, showing a sensitivity and specificity of 0.75 and 0.88 for serum ferritin, while 0.76 and 0.60 for PCT. The CRP level in HFRS with bacterial co-infection (n=115) was higher than that without bacterial co-infection (n=258, p<0.001). The AUC value of CRP for predicting bacterial co-infection was 0.588 (95% CI 0.525-0.652, p<0.001), showing a sensitivity and specificity of 0.43 and 0.76. The serum ferritin level in non-survivors (n=14) was significantly higher than survivors (n=359, p<0.001). The AUC value of serum ferritin for predicting mortality was 0.853 (95% CI 0.774-0.933, p<0.001), showing a sensitivity and specificity of 0.933 and 0.739. Serum ferritin and PCT have robust association with HFRS severity and mortality, which may be as promising predictors, and CRP is an effective biomarker to assess bacterial co-infection in HFRS.